Dynamics of information systems: Mathematical foundations - Sorokin, Alexey (Springer Proceedings in Mathematics & Statistics, 2012)
This proceedings publication is a compilation of selected contributions from the "Third International Conference on the Dynamics of Information Systems" which took place at the University of Florida, Gainesville, February 16-18, 2011. The purpose of this conference was to bring together scientists and engineers from industry, government, and academia in order to exchange new discoveries and results in a broad range of topics relevant to the theory and practice of dynamics of information systems. Dynamics of Information Systems: Mathematical Foundations presents state-of-the art research and is intended for graduate students and researchers interested in some of the most recent discoveries in information theory and dynamical systems. Scientists in other disciplines may also benefit from the applications of new developments to their own area of study.   Information systems play an increasingly critical role in our society; the influence of information on social, biological, genetic, and military systems must be better understood in order to achieve advances in the capability and understanding of these systems. Applications presented in this work are widespread and include research in evolutionary theory, optimization of information workflow, military applications, climate networks, collision work, and much more.